Relationship between Academic Performance and Acquisition of Clinical Skills among Interns in a Government Medical College - Need for Competence Based Medical Education - Sajja Jayashree; SN Manjunatha (Medsci Publications, 2019)
Introduction: Indian Medical Graduate (IMG) should acquire core competencies during the training period. The teaching, learning and assessment methods should be aligned in this direction. Therefore it is necessary to assess medical student's readiness to begin practice as a primary care physician. Objective: To find the relation between academic performance and confidence of performing basic skills. Methodology: A cross sectional study was done on intern medical students using a pre-designed semi-structured questionnaire. A list of 25 clinical skills prescribed for MBBS course as per MCI to function as a primary care physician was used. Results: 52% of the students had an aggregate percentage of marks more than 65. More than 50% of the participants had acquired the basic skills listed except for Insertion of IUD, essential drugs man- agement and management of an epidemic, irrespective of the aca- demic performance. Confidence of handling medico-legal formali- ties was overall low among the study participants. Conclusion: Competence based education and assessment of med- ical students will ensure acquisition of clinical skills and a compe- tent primary care physician.